Experimental Study of Eco-Friendly Concrete by Replacement of Fine Aggregate with Treated Waste Tyre Rubber - Fadzil, Nur Shafiqah; Seyed Hakim, Seyed Jamalaldin (Recent Trends in Civil Engineering and Built Environment, 2025)
Utilizing an alternative fine aggregate in concrete as replacement to natural fine aggregate able to preserve river sand from being excessively dredged as well maintain the sustainability of the environment. This understanding has brought people especially in construction industry to move towards sustainable and green concrete. Currently, a significant portion of discarded tires are disposed of in landfills. Disposal of waste tyres in landfills produces toxic leachate such as Cadmium, Aluminium, Lead, Mercury, Iron, Zinc, Calcium and Barium. These substances are very harmful and causes severe environmental issues. In Malaysia, it is estimated about 417 thousand tonnes of scrap tyres produced each year by 2030. To address this issue, tires are utilized as aggregates in concrete. In this study, crumb rubber is used as a partial substitute for the fine aggregate. It has a size range of 2 to 4 mm and treated using NaOH solution. The main objective of this project is to investigate the impact of incorporating treated waste rubber tyres on the mechanical properties of the concrete, including its workability, compressive strength, and flexural strength. Pre-treatment of crumb rubber is conducted using NaOH solution by 2.5 molarity. The treatment takes 24 hours by soaking crumb rubber into 2.5 molarity of NaOH solution. After that, clean with water and air dried for 24 hours. There are 36 samples which 24 of it is cube sample size 100 mm × 100 mm while another 12 samples are rectangular sample size 100 mm × 100 mm × 400 mm. Regarding rubber, crumb rubber is employed in the experiment to partially replace fine aggregate, with varying percentages by weight of concrete namely, 0%, 5%, 10%, and 15%. The water cement ratio used is 0.54. The result show workability achieved highest value when the percentage of treated crumb rubber increased. Besides, compressive strength value for treated rubberized concrete shows enhancement compared to untreated. Meanwhile, the flexural strength value also achieved higher value than untreated. In conclusion, the treatment of crumb rubber helped to enhance mechanical properties of rubberized concrete due to contact surface between rubber particles and concrete mixture.